1997
DOI: 10.1177/002215549704500613
|View full text |Cite
|
Sign up to set email alerts
|

PDGFRα Expression During Mouse Embryogenesis: Immunolocalization Analyzed by Whole-mount Immunohistostaining Using the Monoclonal Anti-mouse PDGFRα Antibody APA5

Abstract: SUMMARYWe investigated the cells that express platelet-derived growth factor receptor ␣ (PDGFR ␣) during mouse embryogenesis. PDGFR ␣ expression has been identified by in situ hybridization or immunohistochemistry using polyclonal antibodies on tissue sections. Because no immunostaining study using whole-mount specimens has been published to date, we established a new monoclonal antibody (MAb), APA5, for this purpose. Our results differed in that APA5 stained only the paraxial mesoderm, whereas other investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 30 publications
5
119
0
Order By: Relevance
“…Neither mRNA was detected in E9.5 hearts (data not shown). In the literature, Pdgfra has been described without further clarification or attention as being expressed in the embryonic mouse "pericardium," both at the RNA level Schatteman et al, 1992;Lakkis and Epstein, 1998) and at the protein level (Takakura et al, 1997), which from our results we now recognize to be the epicardium. There is also published evidence for low level expression in myocardium (see the Discussion section).…”
Section: Expression Of Pdgfa and Pdgfra In The Mouse Heartmentioning
confidence: 47%
“…Neither mRNA was detected in E9.5 hearts (data not shown). In the literature, Pdgfra has been described without further clarification or attention as being expressed in the embryonic mouse "pericardium," both at the RNA level Schatteman et al, 1992;Lakkis and Epstein, 1998) and at the protein level (Takakura et al, 1997), which from our results we now recognize to be the epicardium. There is also published evidence for low level expression in myocardium (see the Discussion section).…”
Section: Expression Of Pdgfa and Pdgfra In The Mouse Heartmentioning
confidence: 47%
“…Mesp1 GFP ESCs will be a powerful method to screen for new intrinsic and extrinsic regulators of cardiovascular progenitor specifi cation and differentiation. Takakura et al, 1997), and lineage tracing has shown that Flk1 expressing cells give rise to all cardiovascular lineages (Ema et al, 2006), suggesting that these markers could be used in future studies to isolate the early MCPs during mouse embry onic development.…”
Section: Discussionmentioning
confidence: 99%
“…Immunocytochemistry GFP-positive EPCs were subjected to an immunocytochemistry assay as previously described (Takakura et al 1997). In brief, mice were sacrificed under anesthesia by cervical dislocation; the femurs of mice were flushed with PBS and cultured on fibronectin-coated 24-well plates in EGM-2 Supplement Pack with Ang-1 and Ang-2 for 7 days.…”
Section: Measurement Of Vegf Protein In the Conditioned Mediummentioning
confidence: 99%